Mental health professionals' perceptions, judgements and decision-making practices regarding the use of electronic cigarettes as a tobacco harm reduction intervention in mental healthcare: A qualitative focus group study - Smith, Charlie Albert (Addict Behav Rep, 2019)
BACKGROUND: Smoking prevalence remains significantly higher among individuals with mental health conditions compared with the general population. Tobacco harm reduction (THR) in the form of replacing cigarettes for electronic cigarettes (ECs) is an alternative approach which may prove useful for these smokers who find it difficult to quit. Exploring how mental health professionals' (MHPs) perceive ECs, and how these influence decision making regarding their use in clinical settings is essential to determine the feasibility of incorporating ECs into the treatment pathway. METHODS: We conducted six focus groups between March and August 2017. A total of 39 MHPs were recruited from mental healthcare services in England. Discussions were guided by a semi-structured guide, and responses were recorded, transcribed and coded using thematic framework analysis. RESULTS: MHPs generally adopt a risk-averse approach when judging the safety and suitability of ECs. Risk-aversion was influenced by perceived obscurity surrounding ECs and THR, as well as high exposure to adverse and unreliable information regarding ECs, and perceived analogies between ECs and conventional cigarettes. Some MHPs adopt a pragmatic approach when making decisions based on THR and EC use in daily practice by considering the context of treatment and patient circumstances. However, this is often accompanied by a high degree of caution and misconceptions which limits the potential benefit this intervention could have in mental healthcare settings. CONCLUSION: Improved dissemination of national guidance and scientific literature regarding THR and ECs is essential in mental healthcare to eliminate misconceptions and better inform MHPs evidence-based decision-making practices.